Regional movements of satellite‐tagged whale sharks Rhincodon typus in the Gulf of Aden. Issue 9 (23rd March 2021) - Andrzejaczek, Samantha; Vély, Michel; Jouannet, Daniel; Rowat, David; Fossette, Sabrina
Abstract: To gain insight into whale shark ( Rhincodon typus ) movement patterns in the Western Indian Ocean, we deployed eight pop‐up satellite tags at an aggregation site in the Arta Bay region of the Gulf of Tadjoura, Djibouti in the winter months of 2012, 2016, and 2017. Tags revealed movements ranging from local‐scale around the Djibouti aggregation site, regional movements along the coastline of Somaliland, movements north into the Red Sea, and a large‐scale (>1, 000 km) movement to the east coast of Somalia, outside of the Gulf of Aden. Vertical movement data revealed high occupation of the top ten meters of the water column, diel vertical movement patterns, and deep diving behavior. Long‐distance movements recorded both here and in previous studies suggest that connectivity between the whale sharks tagged at the Djibouti aggregation and other documented aggregations in the region are likely within annual timeframes. In addition, wide‐ranging movements through multiple nations, as well as the high use of surface waters recorded, likely exposes whale sharks in this region to several anthropogenic threats, including targeted and bycatch fisheries and ship‐strikes. Area‐based management approaches focusing on seasonal hotspots offer a way forward in the conservation of whale sharks in the Western Indian Ocean. Abstract : Satellite tags reveal local, regional, and large‐scale movement patterns of eight whale sharks tagged at a Djibouti aggregation site. Long‐distance movements suggest that connectivity exists between this site and other documented aggregations in the region.